The effects of supra-normal protein C levels on markers of coagulation, fibrinolysis and inflammation in a human model of endotoxemia - Spiel, Alexander O.; Firbas, Christa; Mayr, Florian B.; Leitner, Judith M.; Schmidt, Bily; Knöbl, Paul; Varadi, Katalin; Jilma, Bernd (Thrombosis and Haemostasis, 2005)
The protein C pathway serves as a modulating system with both anti-inflammatory and anticoagulant properties and is intimately involved in the pathophysiology of inflammation and sepsis. Treatment with recombinant human activated protein C (rhAPC) can reduce the mortality of severe sepsis. We investigated whether an elevation of plasma protein C levels to supranormal levels by infusion of a protein C zymogen concentrate has an effect on coagulation, protein C activation or inflammation in a human endotoxemia model. Eleven healthy male volunteers were enrolled in a double-blind, placebo-controlled two-way cross-over trial. Ten minutes after infusion of 2ng/kg endotoxin each volunteer received either placebo or a plasmaderived protein C zymogen concentrate (Ceprotin®, Baxter) (150 U/kg as a slow bolus infusion followed by 30 U/kg/h continuous infusion until 4 hours after LPS-infusion). Protein C antigen and activity increased 4– to 5-fold after infusion of the concentrate. APC was generated during endotoxin-induced inflammation in the placebo (1.6 fold increase) and the protein C period (4.0-fold increase).The increase of APC levels correlated with the TNF-α and IL-6 release in both periods (r=0.65–0.68; p<0.05) and paralleled the protein C antigen and activity levels in the period with supranormal protein C levels. Supra normal protein C levels resulted in slightly, although non-significant, lower tissue factor mRNA expression and thrombin generation (TAT, F1+2). Systemic inflammation (TNF-α, IL-6) was not influenced by protein C zymogen concentrate administration. Infusion of protein C zymogen was safe and no adverse effects occurred. The increase of protein C levels several fold above the normal range resulted in a proportional increase of the APC levels, but had no major anticoagulant, anti-inflammatory or profibrinolytic effects. Low grade endotoxemia itself induces significant protein C activation, which correlates with the TNF release.
Keywords: Endotoxin; protein C; coagulation; inflammation